Coil design in electric vehicle wireless charging - Huang, Menghui (Nanyang Technological University, 2024)
The magnetic coupling coil is one of the most important components in the wireless power transfer system (WPTs) for charging electric vehicles (EVs), since it determines the energy transfer efficiency of the entire system. Under ideal circumstances, a WPTs has the most efficient energy transfer when the coils are perfectly aligned. However, the misalignment between the EVs charging plate and the underground charging plate is unavoidable in reality. Such misalignment will lead to a sharp reduction in energy transmission efficiency and hinder the popularization of WPT technology. This project conducts simulation of three different structures of coils with varying radii and offsets to evaluate their anti-misalignment performance. Besides, built physical coil structures and verified simulation models by wirelessly charging to power an LED. These experiments proposed a coil design with better anti-misalignment tolerance, offering a comprehensive solution for enhancing charging efficiency in real-world applications.